Beyond landscape experience: A systematic literature review on the concept of spatial quality in flood‐risk management - Bakx, Michiel; Stremke, Sven; Lenzholzer, Sanda (Wiley interdisciplinary reviews. Water, 2023)
People often oppose the implementation of flood mitigation measures based on concerns about “spatial quality” (SQ). SQ can be an ambiguous concept, which can function as boundary object that unites stakeholders from various backgrounds. Yet, the ambiguity of SQ can also be misused to justify particular interests, result in unmet expectations and lead to miscommunication. To contribute to the understanding, communication and implementation of SQ in flood risk management projects, this study systematically reviewed the use of SQ in the literature. The first part of this review resulted in the identification of 19 aspects categorized into four dimensions of SQ: experiential , use , ecological , and long‐term quality . Based on these dimensions , we found in the second part of this review that SQ is understood either as (1) experiential quality only, (2) the combination of experiential , use , and ecological quality , and (3) the combination of all four dimensions . The review illustrates that the understanding of SQ is related to several context characteristics, including the country of author affiliation and the prominent school of thought with regards to objectivity and subjectivity. For example, only authors affiliated with Dutch institutions take into account all four dimensions of SQ. To bridge between these different understandings of SQ, this study provides a framework with a set of terms that can be used for the development of a shared language for SQ, ultimately fostering the implementation of this concept in flood risk management projects. This article is categorized under: Engineering Water > Planning Water